Importance of sexual dimorphism of the maxillary sinus and mandibular inter coronoid distance of Vijayawada City population in Andhra Pradesh: An original research - S Supraja; A Anuradha; Vijaysrinivas Guduru; Mohammad Asif Kiresur; Mohan Kumar Pasupuleti; P Vignatha (Wolters Kluwer Medknow Publications, 2021)
Background: Mass fatality incidents occur due to environmental, medical, vehicle, industrial, or terrorist events that can involve large numbers of victims. Identification of these victims is of utmost importance in these situations. Cone-beam computed tomography (CBCT) may be helpful in some forensic contexts, offering several advantages for postmortem forensic imaging. Aim: The research study aims to evaluate the sexual dimorphism of the maxillary sinus and inter coronoid distance to estimate sex by using CBCT. Materials and Methods: In 40 CBCT scans of 20 males and 20 females, maxillary sinuses height, width and inter coronoid distances of mandible were measured for forensic analysis. In high quality, reconstructed images of bilateral maxillary sinuses, height, and width were measured, and in mandible, inter coronoid was measured in axial view. Results were tabulated and analyzed using an unpaired t-test and discriminant function analysis used to compare differences in the measured parameters between males and females. Results: Mean values of inter coronoid in males and females are (♂ =88.1, ♀ =78.1). The maxillary sinus right side height and width (♂ =32.2, ♀ =24.6) (♂ =19.7, ♀ =19.6) left side height and width (♂ =32.7, ♀ =23.6) (♂ =18.1, ♀ =17.8), respectively. A statistically significant (P < 0.05) difference was found in maxillary sinus and inter coronoid distance between males and females. Results showed significantly larger dimensions of maxillary sinus and inter coronoid distance in males compared to females. The correct predictive accuracy rate of sex determination was 100% in females and 90% in males with overall accuracy of 95%. Conclusion: The present study showed the importance of maxillary sinus dimensions and inter coronoid distance in sex estimation using cone-beam computed tomography in forensic medicine.